2008
DOI: 10.1007/s10565-008-9100-z
|View full text |Cite
|
Sign up to set email alerts
|

Combustion products of 1,3-butadiene inhibit catalase activity and induce expression of oxidative DNA damage repair enzymes in human bronchial epithelial cells

Abstract: 1,3-Butadiene, an important petrochemical, is commonly burned off when excess amounts need to be destroyed. This combustion process produces butadiene soot (BDS), which is composed of a complex mixture of polyaromatic hydrocarbons in particulates ranging in size from <1μm to 1 mm. An organic extract of BDS is both cytotoxic and genotoxic to normal human bronchial epithelial (NHBE) cells. Based on the oxidizing potential of BDS, we hypothesized that an organic extract of this particulate matter would: 1) cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In agreement with our protein expression findings, catalase has been shown to increase in activity with postnatal maturation in the rat lung (Chen and Frank, 1993). Interestingly, exposure of normal human bronchial epithelial cells to butadiene soot, as well as exposure of adult rats to diesel exhaust particles, has been shown to significantly decrease catalase enzyme activity (Kennedy et al, 2009; Rengasamy et al, 2003). Reduction of catalase activity in the rats was thought to be related to the carbonaceous core of the diesel exhaust, a feature that is well preserved in our DFP exposure particles (Rengasamy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our protein expression findings, catalase has been shown to increase in activity with postnatal maturation in the rat lung (Chen and Frank, 1993). Interestingly, exposure of normal human bronchial epithelial cells to butadiene soot, as well as exposure of adult rats to diesel exhaust particles, has been shown to significantly decrease catalase enzyme activity (Kennedy et al, 2009; Rengasamy et al, 2003). Reduction of catalase activity in the rats was thought to be related to the carbonaceous core of the diesel exhaust, a feature that is well preserved in our DFP exposure particles (Rengasamy et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…McGraw et al found exposure to BD metabolites was significantly linked to elevated SBP and endothelial dysfunction, and DHBMA was one of the most important metabolites of the group in relation to SBP and DBP, as indicated by a higher posterior inclusion probability in the Bayesian kernel machine regression model [ 41 ]. Previous experimental studies also revealed that BD exposure may trigger oxidative stress, induce the elevation of reactive oxygen species, and activate the mitochondrial apoptotic pathway [ 42 , 43 ]. Similarly, several epidemiological studies further found positive associations of BD exposure with increased oxidative stress markers, vascular endothelial dysfunction, and several cardiovascular risk factors among the young population in China [ 40 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some factors such as cigarette smoke and other toxicants (i.e., benzene and styrene) may confound the true chronic effects caused by 1, 3-Butadiene exposure [6]. However, 1, 3-Butadiene is a carcinogenic agent, which was reported to cause Deoxyribonucleic Acid (DNA) damage [7,8]. This toxicant metabolically activates the genotoxic epoxides, resulting in abnormality in DNA adducts and chromosomes [9].…”
Section: Introductionmentioning
confidence: 99%